ChemInform Abstract: Photoluminescence and Afterglow of Deep Red Emitting SrSc2O4:Eu2+. Issue 16 (March 2016) - Mueller, Matthias; Volhard, Max‐Fabian; Juestel, Thomas
Abstract: Sr1‐x Sc2 O4 :xEu 2+ (x = 0—0.05) and SrSc2 O4 :Eu 2+, Dy 3+ are prepared by calcination of stoichiometric amounts of SrCO3, Sc2 O3, Eu2 O3, and Dy2 O3 (Mo boat, 1400 °C, 12 h).